Content Analysis of YouTube Videos Knowledge of Biology for Class XI SMA on the GIA Academy Channel - Muyassaroh; Slamet Suyanto (Postgraduate, University of Mataram, 2023)
This article aims to determine the feasibility of learning YouTube content on the subject of Biology. GIA Academy, which is the subject of research in this article, is a channel that provides explanations on various subjects. This research took a sample of 22 video connections with the criteria for class XI Biology lessons from a total of 117 videos. This research uses a content analysis design with the analysis consisting of 4, namely content, presentation, language, and graphics using Krippendorff Theory (2004) with methods in several stages, namely: unitizing, sampling, recording, reducing, inferring, and narrating. The research results show that the overall feasibility of the GIA Academy video is very good or more than 80% with details in terms of content aspects getting 92.04%, presentation aspects 86.04%, language aspects 98.57% and graphics 99.3%.